A PHENOMENOGRAPHICAL STUDY ON PRE-SERVICE SCIENCE TEACHERS’ LEARNING OF CHEMICAL EQUATIONS AND CALCULATIONS - Başak Yaşar ÇETİN (Fırat University, 2019)
The objective of the present thesis is to investigate pre-service science teachers’ learning approach on chemical equations and calculations in detail. The study also aims to clarify the students’ misconceptions about chemical equations and calculations. Thus, educators would be able to better comprehend students’ learning processes in a chemical subject that is considered to be difficult. The main research question of the present thesis is “Which categories could be defined about pre-service science and technology teachers’ learning processes of chemical equations and calculations?” For this purpose, phenomenographical method is utilized. In the context of the study, we aimed to interview students who experienced difficulties in chemistry course and received lower grades in chemistry tests. In this direction, interviews were conducted with 15 pre-service teachers attending Fırat University, Faculty of Education Science Teaching Department who received lower than 50 / 100 in General Chemistry I course midterms. Interviews were conducted in two stages. In the first step, participants were asked a series of questions on chemistry and certain chemical concepts. The second stage of the interviews included a chemistry problem related to chemical equations and calculations, containing limiting reactant. Interview audio recordings, interview transcripts and students’ notes taken during the interviews were analyzed. After the analyses were concluded, descriptive categories were created. What the participants understood about the “Limiting component” concept and their methods to determine the limiting component were separately evaluated. Analysis of the participants’ responses resulted in determination of 5 different desctiptive categories about the “Limiting component” concept, 6 different descriptive categories on their approaches to determine the limiting component, 3 different descriptive categories on their approaches to determine the amount of matter created, and 6 different descriptive categories on “Surplus component” concept. Study results demonstrated that physics and mathematics courses were the courses which the pre-service teachers attending Science Teaching Department did not like the most. Study results also determined that pre-service science teachers had different misconceptions on chemical reactions and calculations.